Case report: Concomitant MitraClip implantation for severe mitral regurgitation and plug closure of endocarditis induced fistula between aortic root and left atrium after transcatheter aortic valve implantation. Issue 1 (21st January 2021) - Ren, Ben; de Jaegere, Peter P T; van Mieghem, Nicolas N M
Abstract: Background: Infective endocarditis (IE) after transcatheter aortic valve implantation (TAVI) occurs in up to 1.5% of patients within the first year. The development of an aorto-atrial fistula (AAF) is a rare but problematic complication of IE, which can be confirmed with transoesophageal echocardiography (TOE). We present an exceptional case of occluding an aorto-left atrial fistula only diagnosed with intraprocedural TOE during a subsequent procedure of MitraClip implantation. Case summary: A 79-year-old symptomatic male patient with multiple comorbidities was referred due to severe mitral regurgitation (MR). He has had prior TAVI which was complicated with streptococcal IE for which he had received prolonged antibacterial therapy. Transthoracic echocardiography (TTE) revealed severe MR. The patient was accepted for a MitraClip procedure by the heart team. Intra-procedural TOE revealed also a significant continuous shunt through an AAF which was likely caused by the endocarditis. The strategy was therefore defined as to occlude the fistula with an Amplatzer Vascular Plug II 12 mm. The plug was released in the fistula leaving an insignificant residual shunt. After the transseptal puncture one MitraClip XTR was implanted, reducing the MR to mild. After the procedure, the patient's general clinical condition improved without signs of haemolysis. The pre-discharge TTE confirmed trace residual shunt, mild residual MR and mild paravalvular leakage. Discussion: Our case illustrates a complex transcatheter structural heart intervention with improvised procedural strategies based on the intra-procedural TOE findings. We conclude that the pre-procedural TOE needs to be comprehensive rather than exclusive, particularly in the context of bioprosthesis-related endocarditis.